Development of Vending Machine Operation System Using Programmable Logic Controller (PLC) - samsuni, muhamad husni bin samsuni; Shaari, Muhammad Farid (Progress in Engineering Application and Technology, 2021)
Vending machine controller is one of the main parts in the vending machine. It acts as the brain which control the flow of the system that allow the consumer to purchase the product from the machine. However, the price for the vending machine controller is not fixed because it depends on the type of operation involved, number of input and output components and last but not least the programming which is the most crucial thing. As the alternative, the cost can be reduced by using the controller that much cheaper and more convenient to integrate the whole system. Therefore, a low-cost beverage vending machine control system has been designed and developed for this project. The programmable logic control (PLC) has been selected as the interface for the note acceptor and the beverage can dispenser. The program was then been generated and tested through the CX-programmer software. The results show the beverage vending machine control system work as designed and the function of dispenser on the beverage can dispenser was verified based on the reliability and consistency test. As the result, the beverage can dispensers are able to dispense all the 26 cans without any distraction which means the system will not encounter any problem until all the beverage can are sold out.